Microstructural origins of high strength and high ductility in an AlCoCrFeNi2.1 eutectic high-entropy alloy. (December 2017) - Gao, Xuzhou; Lu, Yiping; Zhang, Bo; Liang, Ningning; Wu, Guanzhong; Sha, Gang; Liu, Jizi; Zhao, Yonghao
Abstract: Recent studies indicate that eutectic high-entropy alloys can simultaneously possess high strength and high ductility, which have potential applications in industrial fields. Nevertheless, microstructural origins of the excellent strength–ductility combination remain unclear. In this study, an AlCoCrFeNi2.1 eutectic high-entropy alloy was prepared with face-centered cubic (FCC)(L12 )/body-centered-cubic (BCC)(B2) modulated lamellar structures and a remarkable combination of ultimate tensile strength (1351 MPa) and ductility (15.4%) using the classical casting technique. Post-deformation transmission electron microscopy revealed that the FCC(L12 ) phase was deformed in a matter of planar dislocation slip, with a slip system of 111 <110>, and stacking faults due to low stacking fault energy. Due to extreme solute drag, high densities of dislocations are distributed homogeneously at 111 slip plane. In the BCC(B2) phase, some dislocations exist on two 110 slip bands. The atom probe tomography analysis revealed a high density of Cr-enriched nano-precipitates, which strengthened the BCC(B2) phase by Orowan mechanisms. Fracture surface observation revealed a ductile fracture in the FCC(L12 ) phase and a brittle-like fracture in the BCC(B2) lamella. The underlying mechanism for the high strength and high ductility of AlCoCrFeNi2.1 eutectic high-entropy alloy was finally analyzed based on the coupling between the ductile FCC(L12 ) and brittle BCC(B2) phases. Graphical abstract: Image